Bleeding spectrum in children with moderate or severe von Willebrand disease: Relevance of pediatric‐specific bleeding. Issue 12 (17th November 2015) - Sanders, Yvonne V.; Fijnvandraat, Karin; Boender, Johan; Mauser‐Bunschoten, Evelien P.; van der Bom, Johanna G.; de Meris, Joke; Smiers, Frans J.; Granzen, Bernd; Brons, Paul; Tamminga, Rienk Y.J.; Cnossen, Marjon H.; Leebeek, Frank W.G.; et al.
Abstract : The bleeding phenotype of children with von Willebrand disease (VWD) needs to be characterized in detail to facilitate diagnosis during childhood and aid in the planning and assessment of treatment strategies. The objective was to evaluate the occurrence, type, and severity of bleeding in a large cohort of children with moderate and severe VWD. We included 113 children (aged 0–16 years) with Type 1 ( n = 60), 2 ( n = 44), and 3 ( n = 9) VWD with von Willebrand factor (VWF) antigen and/or VWF ristocetin cofactor levels ≤ 30 U/dL from a nation‐wide cross‐sectional study ("Willebrand in the Netherlands" study). Bleeding severity and frequency were determined using the International Society on Thrombosis and Hemostasis‐Bleeding Assessment Tool (ISTH‐BAT) with supplementary pediatric‐specific bleeding symptoms (umbilical stump bleeding, cephalohematoma, cheek hematoma, conjunctival bleeding, postcircumcision and postvenipuncture bleeding). We found that all 26 postmenarche girls experienced menorrhagia. Other common bleedings were cutaneous (81%), oropharyngeal (64%), prolonged bleeding from minor wounds (58%), and epistaxis (56%). Pediatric‐specific bleeding symptoms were present in 44% of patients. ISTH‐BAT bleeding score was higher in index cases than in affected family members (median, 12.0 vs. 6.5, P < 0.001), higher in Type 3 VWD than in Type 2 or 1 (17.0 vs. 10.5 or 6.5, P < 0.001) and higher in children with severe (<10 U/dL) than moderate VWD (10–30 U/dL) (11.0 vs. 7.0, P < 0.001). Frequency of any bleeding, epistaxis, and oral cavity was higher in types 2 and 3 than in Type 1 VWD and was associated with VWF levels. We conclude that pediatric‐specific bleeding symptoms occurred in a large proportion of children with moderate or severe VWD and should be included when evaluating children for VWD. Am. J. Hematol. 90:1142–1148, 2015. © 2015 Wiley Periodicals, Inc.